Autoimmune manifestations in children with inborn errors of immunity in Morocco: A study from the national registry - Ahamada Elamine; Ibtihal Benhsaien; Fatima Ailal; Abderrahmane Errami; Zakaria Kasmi; Zahra Aadam; Asmaa Drissi Bourhanbour; Ahmed Aziz Bousfiha; Jalila El Bakkouri (Journal of Translational Autoimmunity, 2025)
Inborn Errors of Immunity (IEI) are a heterogeneous group of genetic disorders characterized by increased susceptibility to infections and immune dysregulation, including autoimmunity and autoinflammation. Despite their clinical significance, data on autoimmune manifestations in Moroccan pediatric patients with IEI remain limited.This study aims to investigate the prevalence, spectrum, and clinical patterns of autoimmune manifestations in pediatric patients with IEI in Morocco.We conducted a retrospective analysis of pediatric patients registered in the Moroccan IEI registry from January 2007 to December 2023. Demographic, clinical, and laboratory data were extracted, with a particular focus on autoimmune manifestations.Among 769 patients registered in the Moroccan IEI registry, 108 (14 %) exhibited at least one autoimmune manifestation. Consanguinity was observed in 59 (55 %) of cases, and the male-to-female ratio was 1.14. The median age at the onset of clinical symptoms was 10 months (2–33 months), and the median age at IEI diagnosis was 30 months (10.5–84 months). A total of 191 autoimmune manifestations were recorded among these patients, with a notable predominance of autoimmune cytopenia (72 %), followed by cutaneous (10 %) and gastrointestinal (9 %) manifestations. Poly-autoimmunity was present in 47.3 % of affected patients. The most frequently associated IEI subtype with these autoimmune manifestations was common variable immunodeficiency (16,7 %).Autoimmune manifestations are a frequent complication in Moroccan children with IEI, with autoimmune cytopenias predominating. A high index of suspicion for IEI should be maintained in patients initially presenting with autoimmunity, particularly autoimmune cytopenia. These patients require personalized management due to their higher risk of mortality.